Bullying Types for Lombok Island Middle School Students and Solutions to Reduce It - Agus Ramdani; I Putu Artayasa; Jamaluddin Jamaluddin (IKIP Mataram, 2021)
At this time in the educational environment there have been many worrying behaviors and acts of violence. One of the most frequent acts of violence is bullying behavior. The prevalence of bullying behavior that has increased from year to year has caused damage or adverse impacts for both the perpetrator and the victim. This study aims to describe bullying among students and actions to minimize it on the island of Lombok, which consists of Mataram City, West Lombok Regency, Central Lomok, East Lombok and North Lombok. The subjects of this study were the principal, class teacher, class students, BK teachers, and parents of students. Data collection techniques used documentation studies, questionnaires, observation sheets, and interview techniques. The data analysis technique uses three activity lines, namely data reduction, data presentation and conclusion drawing and uses data validity tests using data triangulation tests. The results showed that some students had been involved in bullying behavior. Of the three forms of bullying behavior, the verbal form is the most common bullying behavior in schools. In this study it was also found that the three aspects of bullying behavior, namely, carried out intentionally with or without a specific purpose, there is an element to hurt the victim, there is an imbalance of power and/or strength between the perpetrator and the victim of bullying, and it occurs repeatedly which is fulfilled. Efforts to minimize bullying is by planting character education which must be implemented in the learning process.